Survival of common carp carrying Cyca-DAB1*05 post-challenged with Aeromonas hydrophila - Arsal, Laode Muhammad; Yuhana, Munti; Nuryati, Sri; Alimuddin, , (Indonesian Society of Scientific Aquaculture (ISSA), 2014)
ABSTRACT Blood parameters are considered as important indicators to diagnose fish health status. This study was performed to observe blood profiles including total erythrocytes, hemoglobin concentration, hematocrite, total leukocytes and differential leukocytes, and survival of common carp Cyprinus carpio infected by Aeromonas hydrophila. Fish were divided into two groups: the 3rd generation of common carp carrying fish carrying Cyca-DAB1*05 of major histocompatibility complex II molecular marker, and fish without the marker as control treatment. histocompatibility complex II molecular marker, and fish without the marker as control treatment. Common carp 3rd generation was produced by crossing among second generation of fish carrying the Cyca-DAB1*05 marker. Each fish was injected intramuscularly by 0.1 mL of 108 cfu/mL A. hydrophila. Challenge test was conducted for 14 days and blood was collected at day-0, three, seven, and 14. The results of this study showed that erythrocytes, hemoglobin and hematocrite concentrations of common carp carrying the molecular marker at post challenge with A. hydrophila were higher (P<0.05) compared to control fish. The blood profiles were highly correlated to survival of fish. Survival of fish that carrying the molekuler marker was about two point six fold higher than those of control fish. Keywords: Cyprinus carpio, Aeromonas hydrophila, Cyca-DAB1*05, molecular marker ABSTRAK Gambaran darah merupakan indikator penting untuk mendiagnosa penyakit ikan. Penelitian ini dilakukan untuk meguji gambaran darah ikan mas Cyprinus carpio setelah diinfeksi dengan bakteri Aeromonas hydrophila yang meliputi total sel darah merah, konsentrasi hemoglobin, hematokrit, total sel darah putih, dan diferensial leukosit, serta sintasannya. Ikan mas yang digunakan terdiri atas ikan mas generasi ketiga yang membawa marka molekuler Cyca-DAB1*05 dari kelompok major histocompatibility complex II dan ikan mas tanpa marka sebagai kontrol. Ikan mas generasi ketiga merupakan keturunan persilangan antarikan mas generasi kedua yang mempunyai marka Cyca-DAB1*05. Masing-masing ikan diinfeksikan A. hydrophila secara intramuskuler pada dosis 0,1 mL, kepadatan 108 cfu/mL. Uji tantang dilakukan selama 14 hari, dan sampel darah ikan diambil pada hari ke-0, tiga, tujuh dan 14. Hasil uji tantang menunjukkan bahwa total sel darah merah, konsentrasi hemoglobin dan hematokrit pada ikan mas yang membawa marka molekuler lebih tinggi dibandingkan ikan mas tanpa marka (P<0,05). Hasil uji gambaran darah berkorelasi tinggi dengan tingkat kelangsungan hidup ikan mas. Tingkat kelangsungan hidup ikan mas yang membawa marka molekuler Cyca-DAB1*05 lebih tinggi hingga dua koma enam kali daripada ikan mas kontrol. Kata kunci: Cyprinus carpio, Aeromonas hydrophila, Cyca-DAB1*05, marka molekuler